An Analysis of Language Changes in the Family Environment - Gusta, Wienda; Alhusna, Asma; Febriana, Noni; Afersa, Mona (Fakultas Sastra Universitas Ekasakti, 2024)
Language change is a process in which a language changes due to changes in the structure of its linguistic elements. This happens because there are factors that trigger language changes, and of course one of the factors is also due to the development of the times. This research aims to analyze language change that is sound change and differences in meaning. This research was done by interviewing parents and one of our friends. It uses a qualitative research method that analyzes several related Google journals and sources. The research results show that sound change and differences in meaning are parts of language change. The development of the times affects the change of language. In the family, it should be used in a polite tone so that it can be well received. The difference in meaning between the past and now is very different. For example, in the family environment, disagreements often occur between parents and children due to changing times. A child's intentions are often not heard and denied by parents, and vice versa.